2021
DOI: 10.1186/s12985-021-01509-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory siRNA with a uridine bulge leads to potent inhibition of HBV and activation of innate immunity

Abstract: Background Hepatitis B virus (HBV) infection is difficult to cure. HBV-specific immune tolerance plays a key role in HBV persistence, and enhancing cellular and humoral immunity will improve the control of HBV infection. The purpose of the study was to explore the anti-HBV and immunostimulatory effects of msiRNAs that introduce unpaired uridine bulges in the passenger strand. Methods msiRNAs targeting the HBV S and X genes were designed and named m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The results of HE staining of the heart, liver, spleen, kidney, brain and lung sections from the PSN-treated mice showed that PSN intervention could improve liver injury in HBV-infected mice without other organ damage, which indicated that the efficacy and safety of PSN were not in doubt. For the antiviral effect of PSN, we found that the levels of HBV DNA, HBeAg and HBsAg in the PSN-treated hepatitis B mice group were significantly lower than those in the model group, which is consistent with the results of related studies that siRNA can significantly reduce the levels of HBeAg and HBsAg in vivo (7,38). Furthermore, we discovered that PSN lowered ALT and AST levels in hepatitis B mice, confirming the antiviral action of PSN in vivo and improving liver function to some extent.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of HE staining of the heart, liver, spleen, kidney, brain and lung sections from the PSN-treated mice showed that PSN intervention could improve liver injury in HBV-infected mice without other organ damage, which indicated that the efficacy and safety of PSN were not in doubt. For the antiviral effect of PSN, we found that the levels of HBV DNA, HBeAg and HBsAg in the PSN-treated hepatitis B mice group were significantly lower than those in the model group, which is consistent with the results of related studies that siRNA can significantly reduce the levels of HBeAg and HBsAg in vivo (7,38). Furthermore, we discovered that PSN lowered ALT and AST levels in hepatitis B mice, confirming the antiviral action of PSN in vivo and improving liver function to some extent.…”
Section: Discussionsupporting
confidence: 90%
“…The standard curve for HBV DNA was plotted using Ct values and the copy number was converted to international unit IU/mL. After centrifuging the supernatant, 50 mL was transferred to a new PCR tube, heated at 100°C for 2 min, then 1 mL was taken into the qPCR system (7), and the level of HBV DNA was calculated using the standard curve. After centrifugation to remove cell debris, the supernatant was obtained and HBsAg ELISA kits (Keygen Biotech, Co., Ltd) were used to detect HBV antigen levels according to the kit instructions.…”
Section: Cellular Assay Of Hbv Inhibition By Sirnamentioning
confidence: 99%
See 1 more Smart Citation